A general route to fluorinated 3, 3-disubstituted 2-oxindoles via a photoinduced radical cyclization of N-arylacrylamides under catalyst-free conditions. Issue 5 (9th March 2016) - An, Yuanyuan; Li, Yuewen; Wu, Jie
Abstract : A catalyst-free radical cyclization of N -arylacrylamides with fluorinated alkyl iodides or the Togni reagent enabled by photoenergy is reported, leading to fluorinated 2-oxindoles in good yields. The broad reaction scope is demonstrated with good functional group tolerance. Abstract : A catalyst-free radical cyclization of N -arylacrylamides with fluorinated alkyl iodides or the Togni reagent enabled by photoenergy is presented for the first time. Under ultraviolet irradiation, the generation of fluorinated 3, 3-disubstituted 2-oxindoles proceeds smoothly without any metals or photoredox catalysts. The broad reaction scope is demonstrated with good functional group tolerance. During the process, fluorinated alkyl groups can be easily incorporated.